2011
DOI: 10.1029/2011gc003848
|View full text |Cite
|
Sign up to set email alerts
|

Rock magnetic properties of a soil developed on an alluvial deposit at Buttermilk Creek, Texas, USA

Abstract: [1] The evolution of magnetization within a floodplain soil begins with initial deposition of magnetic particles during sedimentation and continues via subsequent alteration and growth of iron-bearing compounds by pedogenic and biologic processes. Measurements of soil magnetic properties capture information about the developmental history of the soil and are a convenient method by which to investigate environmental change and pedogenesis. Using a range of magnetic measurements, a comprehensive scenario for soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Because the T v is absent in the ZFC/FC plots, we suggest that maghemite, not magnetite, is the magnetically soft SD grain primarily responsible for much of the increased magnetic susceptibility in the soil horizons. Lindquist et al (2011) document a similar ZFC/FC pattern from alluvial soils in Texas and suggested it could be the results of goethite and SP maghemite. In this study however, the RT-SIRM suggests the presence of stoichiometric magnetite in the T3 terrace and the irreversible warming of all RT-SIRM analyses indicates the presence of PSD maghemite in all terraces (Figure 6), suggesting a difference in magnetic mineralogy between our Delaware River valley soils and those of Lindquist et al (2011).…”
Section: Discussion Magnetic Enhancement In Delaware Alluvial Soilsmentioning
confidence: 91%
See 3 more Smart Citations
“…Because the T v is absent in the ZFC/FC plots, we suggest that maghemite, not magnetite, is the magnetically soft SD grain primarily responsible for much of the increased magnetic susceptibility in the soil horizons. Lindquist et al (2011) document a similar ZFC/FC pattern from alluvial soils in Texas and suggested it could be the results of goethite and SP maghemite. In this study however, the RT-SIRM suggests the presence of stoichiometric magnetite in the T3 terrace and the irreversible warming of all RT-SIRM analyses indicates the presence of PSD maghemite in all terraces (Figure 6), suggesting a difference in magnetic mineralogy between our Delaware River valley soils and those of Lindquist et al (2011).…”
Section: Discussion Magnetic Enhancement In Delaware Alluvial Soilsmentioning
confidence: 91%
“…The ratio of ARM to IRM (ARM/IRM) provides a relative estimate of the fine-grained SD-like particle concentration (King et al, 1982;Geiss et al, 2004;Lindquist et al, 2011). Because the S-ratio and backfield remanence suggest the presence of a lowcoercivity mineral such as magnetite or maghemite, we can infer the ARM/IRM ratio indicates changes in the relative concentration of fine-grained magnetite/maghemite.…”
Section: Magnetic Remanencementioning
confidence: 99%
See 2 more Smart Citations
“…At GS1, the χfd% (~10%) resembles percentages typical of modern soils rich in organic carbon. While most natural soils show a progressive decrease in the abundance of SP grains with depth (Lindquist et al 2011), the samples at GS1 show consistently elevated and stable SP concentrations. This further indicates that the sediments are not an expression of natural environmental processes but that human occupation played an important role in the formation of the magnetic assemblage.…”
Section: Discussionmentioning
confidence: 94%